Laut Cina Selatan: Menakar Peran Indonesia Dalam Dewan Keamanan United Nation: International Dispute Resolution; South China Sea; UNCLOS 1982. - Rihardi, Satrio Ageng; Pembayun, Jaduk Gilang; Yusliwidaka, Arnanda (PROGRESIF: Jurnal Hukum, 2022)
Indonesia has been elected as a Non-Permanent Member of the United Nations Security Council (Non-Permanent Member of the UN Security Council) in the 2019-2020 period. This is an extraordinary achievement, considering that Indonesia is trusted by UN member countries to be one of the members of the UN Main Organ which has the task of maintaining world peace and security. The South China Sea (LTS) is an area that is being disputed between neighboring countries that feel they have a claim to the area. This dispute has become the world's attention where the tensions shown by these countries are increasingly worrying about security stability in the region. Various provocations and foreign policies from each country were carried out to win claims to the territory. Indonesia as a non-permanent member of the UN Security Council has one of the obligations to participate in resolving international disputes over the LTS area which is claimed by countries. Indonesia can be a mediator to provide another point of view in resolving the dispute peacefully. The purpose of this study is to examine Indonesia's involvement in efforts to resolve disputes in the South China Sea region based on the 1982 United Nations Convention on the Law of the Sea (UNCLOS 1982). The method used in this research is normative legal research. This research was conducted by researching and reviewing library materials that had been collected by the research team. The library materials that were researched and studied consisted of primary materials, secondary materials, and tertiary materials. Data search is done by literature study or document study and all data obtained will be analyzed qualitatively